Employee engagement : a practical introduction - Bridger, Emma (Kogan Page Limited, 2018)
Equip yourself with the knowledge and tools to build, drive and measure employee engagement with this essential guide from the HR Fundamentals series.- Resumé vydavatel
Keywords: personální management; pracovní motivace; organizační chování; personnel management; employee motivation; organizational behavior; elektronické knihy; příručky; případové studie; electronic books; handbooks and manuals; case studies